Is It Truly Myopia or Pseudomyopia?: A Case Report of a Pediatric Patient - Intaniasari, Webby Bernica; Deneska, Ria Sandy (Asian Journal of Health Research, 2024)
Introduction: Pseudomyopia, resulting from excessive accommodation or nerve-related effects, creates false myopia corrected by cycloplegic refraction, which differs from secondary myopia caused by identifiable factors such as cataracts or trauma. If underlying hyperopia remains undetected, symptoms such as asthenopia and headaches occur, potentially resulting in conditions such as amblyopia. We presented a case of pseudomyopia in a pediatric patient to describe its clinical features and treatment. Case Presentation: A 7-year-old patient, who often uses smartphones for approximately 1–3 h daily in a well-lit room, initially reported blurry distant vision, headaches, eye discomfort, and difficulty reading from a distance. At the first visit, the visual acuity of the right (oculus dexter, OD) and left (oculus sinister, OS) eyes was 6/18 and 6/24, respectively. A cycloplegic was administered to both eyes, and subjective refraction of OD S +1.00 and OS S +1.25 was obtained. The patient was diagnosed with pseudomyopia and was administered glasses treatment and cycloplegic topical eye drops. After 12 weeks of treatment, the best-corrected visual acuity was 6/6. Conclusion: Pseudomyopia clinical features in pediatric patients could vary and should be distinguished from accommodative spasms. Treatment approaches vary widely, reflecting the lack of consensus on management despite consistent assessment and diagnostic approaches.